Research progress on complications of Brucellosis - Jin, Min; Fan, Zixu; Gao, Ruifang; Li, Xingnan; Gao, Zhixiang; Wang, Zhanli (Frontiers in Cellular and Infection Microbiology, 2023)
Brucellosis, referred to as brucellosis, is a zoonotic disease caused by Brucella infection and is spread globally. The clinical characteristics of the disease are fever, sweating, malaise, myalgia, arthralgia, loss of appetite, weight loss, enlargement of liver, spleen and lymph nodes, and other non-specific symptoms. The disease has a long and recurrent course, and often accumulates in multiple systems and organs, posing a significant health threat to the animals and humans. Brucella osteoarthropathy is the most common complication, often manifested as spondylitis, sacroiliac arthritis, and peripheral arthritis. In the digestive system involving the liver and the spleen, liver is the largest endothelial reticular system, and patients are often accompanied by hepatic granulomatous inflammation. Although respiratory system involvement is less common, pneumonia, pleurisy, pleural effusion, and pulmonary nodulosis have been reported. The genitourinary system infection is mainly unilateral in men. The cardiovascular system faces the most serious complication of brucellosis, and >80% of deaths are related to infective endocarditis. The hematologic system is affected in children, often manifesting as anemia, leukopenia, and complete blood cytopenia. The neurologic system complications consist mainly of meningitis. In this study, we reviewed the multisystem complications of brucellosis, aiming to improve the understanding of the disease among medical workers, in the hope of early diagnosis, timely treatment, and prevention of long-term complications.